DOES ENERGY DRINK INTAKE BEFORE EXERCISE AFFECT NONLINEAR DYNAMICS OF HEART RATE VARIABILITY RECOVERY? A RANDOMIZED, CROSSOVER, DOUBLE-BLIND AND PLACEBO-CONTROLLED TRIAL - Porto, Andrey Alves [UNESP]; Gonzaga, Luana A. [UNESP]; Benjamim, Cicero Jonas R. [UNESP]; Cardoso, Vinicius Ferreira [UNESP]; Garner, David M. [UNESP]; Ferreira, Celso [UNESP]; Bueno Junior, Carlos Roberto [UNESP]; Valenti, Vitor Engracia [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2023)
Introduction and Objectives: Energy drinks (ED) are recognized to influence the behavior of the sympathetic and parasympathetic components of the autonomic nervous system. We intended to study the influence of ED on non-linear heart rate variability (HRV) following exercise. Material and Methods: This randomized, crossover, double-blind, placebo-controlled clinical trial (Protocol number NCT02917889) was completed in a sample of 28 healthy males aged 24.11 +/- 3.05 years (min-max 18-29). The first step involved the assessment of maximal oxygen consumption (VO2 max). In the second protocol, the subjects received a placebo (250ml of water) or ED (250ml of energy drink) 15 minutes before the 30-minute exercise on a treadmill. In the third protocol, participants received the alternative protocol to the previous step. The nonlinear HRV were calculated at different times during the protocols. Results: Fractal analysis via Detrended Fluctuation Analysis (DFA) revealed that in the placebo protocol there was an increase in its values compared to recovery (Rec1) vs. Rest (Cohen's d= 1.42) and continued increasing in the last recording intervals: vs. Rec6 (Cohen's d= 0.70) and vs. Rec7 (Cohen's d= 0.85). In the ED protocol, the increase in DFA was only demonstrated when comparing Rec1 vs. Rest (Cohen's d=1.78). Conclusion: ED intake prior to modest aerobic exercise triggered a slight acceleration of recovery.
Keywords: Energy drink; Exercise; Heart rate variability; Nonlinear dynamics